Personality Traits, Hedonic Motivation and Self-Control on Impulsive Buying: A Systematic Literature Review - Fadhila, Risa; Dwita, Vidyarini (Formosa Journal of Multidisciplinary Research, 2024)
This article aims to identify and analyze key references on impulsive buying behavior influenced by individual personality traits, hedonic motivation, and self-control. This study employs a systematic literature review using the Google Scholar database (including Emerald, ProQuest, and ResearchGate) via Harzing's Publish or Perish software. Data were analyzed using Microsoft Excel, Mendeley, and VOSviewer. The study follows the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach, resulting in 16 core articles. The findings reveal six scientific clusters supporting research on personality traits, hedonic motivations, self-control, and impulsive buying behavior, with a total of 164 link strengths. The VOSviewer visualization demonstrates that impulsive buying and consumer behavior are dominant keywords, serving as central nodes connecting personality traits and self-control. Meanwhile, the keyword hedonic motivation appears smaller in size and less prominent.